How University Professors Assess Their Teaching Experience at Schools - E. A. Popov (Высшее образование в России)
The problem of interaction between general education schools and higher education institutions is one of the most relevant for interdisciplinary research. For this reason, the purpose of the article is not only to evaluate the experience of University professors in modern schools, but also to consider one of the possible mechanisms for improving the intellectual culture of schoolchildren. Universities’ request for the intellectualism of their students cannot be dissociated from the mission of school. Therefore, the article analyzes some of the possibilities of professors working both at Universities and at schools at least five years, to improve the continuity between schools and universities. The professors’ experience of working as school teachers is considered both as a subjective factor (“the desire to feel young”) and as an objective one, aimed at working with gifted young people, with students who are ready to continue their studies at Universities in the future. The article used the method of online survey with the participation of 50 professors of the Russian classical universities. The main requirement for respondents was to combine the positions of school teacher and University professor for at least 5 years. 232 professors had such experience, but not all of them were able to take part in the study. The results of the study can be summarized in the following main provisions: 1) the professors evaluate their teaching experience as a positive not only from the perspective of one’s personal development, but also as a contribution to the development of educational strategies ensuring continuity between schools and universities or their constructive cooperation; 2) the participation of professors in school life significantly affects the quality of schooling, and contributes to the formation of the academic principle in the school environment; 3) the professors’ teaching experience is also important for universities (e.g., students).